COMPARATIVE ANALISYS OF TAX SYSTEMS OF SCANDINAVIAN AND MEDITERRANEAN COUNTRIES - Jeremić, Nebojša O; Kamenković, Sandra S; Grubišić, Zoran (Poslovna ekonomija, 2019)
Mutual differences between modern tax systems are conditioned by, first of all, the political and economic organizations of the state. Taking into account not only economic, but also social and political specifics of southern and northern Europe, and having in mind three main objects of taxation in the tax system of the country (consumption, income and assets), this paper analyses how structured are tax systems of different European regions. The countries of the north and south of Europe, despite the harmonization of taxes within the EU, are still characterized by numerous specificities in tax systems. Differences arise from combinations of direct and indirect taxes, with the aim of achieving optimal economic growth, macroeconomic stability and more even distribution of income that tax authorities of Scandinavian and Mediterranean countries want to achieve. The share of the collected income tax in GDP, which is higher in the countries of the north of Europe, including corporate income taxes, offset the Mediterranean countries by a higher share of social contributions to income and collecting property taxes. The Scandinavian countries, known as the generous welfare states, show that they are not among the countries with the highest tax burden on labour.